Analysis of the Expository Text Structure in Indonesian Language Textbooks - Muammar (Jurnal Wawasan Sarjana, 2025)
This study originates from the significance of expository texts in Indonesian language textbooks as a medium to enhance students’ reading comprehension, critical thinking, and academic literacy. However, variations in structure, cohesion, coherence, and text complexity often pose challenges in the learning process. The purpose of this research is to analyze the structure of expository texts in Indonesian language textbooks, identify their strengths and weaknesses, and provide practical recommendations for teachers and curriculum developers. The study employed a qualitative approach using content analysis design. Data were collected through purposive sampling of Indonesian language textbooks used across different educational levels. The analysis focused on structural elements (thesis, arguments, evidence, and conclusion), cohesion and coherence devices, as well as levels of text complexity. The findings reveal that most expository texts follow the classical pattern of thesis–argument–evidence–conclusion, yet inconsistencies remain in the use of cohesion devices, logical flow, and variations of text complexity across grade levels. These factors significantly affect students’ comprehension and engagement. The study emphasizes the importance of teacher scaffolding, progressive sequencing of materials, and explicit training in text analysis to strengthen students’ critical literacy and academic skills.